Small Molecules with Potential Biological Activities - Akhtar, Muhammad Nadeem; Swee, Keong Yeap; Seema, Zareen; Siti Noor Hajar, Zamrus; Addila, Abu Bakar; Saiful Nizam, Tajuddin; Noorjahan Banu, Alitheen (2016)
Natural products are unique source for drugs discovery. Several small molecules such as anthraquinones flavokawain B and curcumin related compounds exhibited tremendous biological activities. Curcumin and related compounds containing 1,3-diketone moiety, which is also essential biological activities possessing various pharmacological activities such as anti-cancer, anti-inflammatory, anti-oxidant and anti-diabetic properties. Various naturally occurring compounds have been synthesized and investigated for their cytotoxic properties against breast cancer cell lines MDA-MB231 cells. A series of mono-carbonyl curcuminoids analogs have been synthesized by Claisen Schmidt condensation reaction by using acid or base catalysed reaction. Various analogues especially 2,6-bis(4-bromobenzylidene)cyclohexanone, 1,5-bis(4-hydroxy-3- methoxyphenyl) penta-1,4-dien-3-one and 1,5-bis(2,5-dimethoxyphenyl)penta-1,4-diene-3- one showed the potential anticancer activity. Together, these results some natural compounds isolated from Knema laurina showed acetylcholinesterase inhibitory activities. The compounds were purified by column chromatography and their structures were determined by 1H NMR, GC-MS, and single X-ray analysis techniques.